2022
DOI: 10.47352/jmans.2774-3047.101
|View full text |Cite
|
Sign up to set email alerts
|

Review on Calixarene Fluorescent Chemosensor Agents for Various Analytes

Abstract: Calixarenes are well-known supramolecular host molecules with versatile applications. Over the past decades, hundreds of selective and sensitive detections of several analytes have been reported by employing calixarenes as the chemosensor agent. The detection and quantification of metal ions and anions are crucial as heavy metal ions are harmful to living organisms, while monitoring anions is pivotal in the environmental samples. On the other hand, detecting and quantifying biomolecules and neutral molecules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
(56 reference statements)
1
1
0
Order By: Relevance
“…On the other hand, the neutral PABA molecule could be detected by calixarene through the formation of hydrogen bonding between PABA and phenoxy O atoms from calixarenes. These interactions are supported by the studies made by previous researchers regarding the interaction between calixarenes with ions and neutral molecules (De Leener et al, 2022;Fahmy et al, 2018;Pellegrini, 2011;Priyangga et al, 2022).…”
Section: Host-guest Sensing Interactions Of Calix[n]arene-paba Complexessupporting
confidence: 75%
“…On the other hand, the neutral PABA molecule could be detected by calixarene through the formation of hydrogen bonding between PABA and phenoxy O atoms from calixarenes. These interactions are supported by the studies made by previous researchers regarding the interaction between calixarenes with ions and neutral molecules (De Leener et al, 2022;Fahmy et al, 2018;Pellegrini, 2011;Priyangga et al, 2022).…”
Section: Host-guest Sensing Interactions Of Calix[n]arene-paba Complexessupporting
confidence: 75%
“…However, many of them have low solubility, poor recognition sensitivity, and complex synthesis under extreme conditions. 36 As a result, there is always room for improvement in designing probes to overcome these constraints. Schiff bases or imines are one type of compound that has been highlighted in many fields of chemistry due to its ease of synthesis and structural modification.…”
Section: S Gayathrimentioning
confidence: 99%
“…Priyangga et al [26] reported that calix [4] resorcinarenes could form a stable chelate complex with iron metal ions through their hydroxyl groups. On the other hand, Sari et al [19] reported that hydroxyl groups of calix [4]pyrogallolarenes interacted with iron center ion and carboxylic group of heme, thus inhibiting its polymerization process.…”
Section: In Vitro Antimalarial Assaymentioning
confidence: 99%